Impacts of myosin heavy chain phenotypes on recovery of leg extension force after ACL-reconstructed knee - Tetsuo Kobayashi; Yuji Ogura; Satoshi Kishiro; Mitsutoshi Kurosaka; Toshinori Yoshihara; Ryo Kakigi; Naoki Minakawa; Kenji Uehara; Tomohiro Suzuki; Katsumasa Goto; Hisateru Niki (Japanese Society of Physical Fitness and Sports Medicine, 2023)
It is well known that myosin heavy chain (MyHC) phenotypes impact skeletal muscle function. Anterior cruciate ligament (ACL) tear, a common sport injury, induces skeletal muscle atrophy around the injured knee. However, the interrelationship between MyHCs and the functional recovery of ACL reconstruction surgery (ACL-R) remains unclear. The purpose of this study was to investigate the interrelationship between MyHC phenotypes and the functional recovery of leg extension force in patients with ACL-R. Under a clinical setting, 27 patients with ACL-R participated in this study. ACL-R in each patient was carried out using a semitendinous (ST) tendon autograft. During ACL-R, a small muscle sample was dissected from the ST tendon of each patient. MyHC phenotypes in the muscle sample were evaluated using SDS-PAGE. The leg extension force was evaluated 1 day before and then 3, 6, and 12 months after ACL-R. Based on the dominant (>40%) MyHC isoforms in the ST muscle, patients were classified into 4 groups as follows: Groups I, IIa, IId/x, and Even (E: all MyHC isoforms less than 40%). There is a positive correlation between the relative content of MyHC II (IIa + IId/x) and the leg extension force before ACL-R. Functional recovery of knee in subjects with ACL-R was facilitated in patients having the dominant MyHC IIa. This study suggests that the analysis of MyHC phenotypes in ST muscle dissected during ACL-R is a clinically useful index for the functional assessment of the knee in subjects with ACL injury.